Antiplatelets in Secondary Stroke Prevention - Shulga, Olga; Bornstein, Natan (Frontiers in Neurology, 2011)
The aim of this review is to provide evidence-based recommendations on the secondary prevention of atherothrombotic ischemic stroke. Antiplatelets are the major therapy for the secondary stroke prevention. The most commonly used antiplatelets agents are aspirin, clopidogrel and extended-release dipyridamol. A lot of progress had been made in last years regarding aspirin resistance and genotyping of clopidogrel metabolism. According to the results of the accomplished studies it is difficult to broadly recommend one antithrombotic agent in favor of the other. Instead, a review of the currently published data suggests the importance of focusing on the individualizing approach in antiplatelet therapy.